(3GdLGeY dCNdGb GdQGhj hBOGH GdSGeYs - (3GdNWjH GdHZOGOj , CMeO Hf Ydj Hf KGHJ , CHh HcQ , J (B463 (3g` s
(3ChdgG (B:s
(3CeG HYO abO PcQJ aj cJGH TQa CUMGH GdMOjK hGdELJgGO aj WdHgG hGdMQU Ydi SeGYgG s
(3BNQgG (B:s
(3agh jLQi Ydjg ef GdCLQ eG cGf jLQi Ydjg aj THjHJg hUMJg gPG BNQ GdcJGH s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B172s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B575s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
Keywords: (3GdMOjK h GdeUWdMs